Perioperative noninvasive cardiac output monitoring in parturients undergoing cesarean delivery with spinal anesthesia and prophylactic phenylephrine drip: a prospective observational cohort study. (2nd October 2019) - Orbach-Zinger, Sharon; Bizman, Ilya; Firman, Shlomo; Lev, Shaul; Gat, Roi; Ashwal, Eran; Vaturi, Mordehay; Razinski, Eitan; Davis, Atara; Shmueli, Anat; Eidelman, Leonid A.
Abstract: Introduction: Spinal anesthesia for cesarean delivery is associated with high incidence of hypotension and is most often prevented by a prophylactic phenylephrine infusion (PPI). In this study, we aimed to identify maternal hemodynamic changes both intraoperatively and postoperatively with the use of the NICaS noninvasive cardiac output monitor in healthy singleton parturients undergoing cesarean delivery (CD) with spinal anesthesia and PPI. Methods: Healthy term women undergoing spinal anesthesia for singleton CD were enrolled. The following data were collected – cardiac output (CO), mean arterial pressure (MAP), stroke volume (SV), and total peripheral resistance (TPR). Measurements were measured at five time points: (1) before arrival in OR, (2) after spinal anesthesia with pi, (3) after delivery of baby and beginning of oxytocin infusion, (4) in post anesthesia care room (5) 24 hours postoperatively, and (6) 48 hours postoperatively. All parturients received standardized spinal solution consisting of 12 mg hyperbaric, 20 µg fentanyl, and 100-µg preservative-free morphine. PPI was titrated to preserve blood pressure to 20% of baseline and stopped at the end of surgery. Oxytocin was administered as a continuous infusion (20-units/1000 cc Ringer lactate) at a rate of 100 cc/h. Results: One hundred thirty-seven women completed the study. Average age was 34.9 ± 5.7 and average BMI was 30.1 ± 5.1. One hour after delivery in the post anesthesia care unit (PACU), there were significant decreases in stroke volume, heart rate, blood pressure, and CO with a concomitant increase in TPR. Within 48 hours the TPR decreased, and CO and stroke volume increased. Conclusions: Significant hemodynamic changes were documented at all time points both intraoperatively and postoperatively with the most significant changes occurring 1 hour postoperatively. Further studies need to be performed to discover hemodynamic changes of spinal anesthesia and PPI in different parturient populations.